A Preclinical Assessment of Early Continuous Passive Motion and Treadmill Therapeutic Exercises for Generating Chondroprotective Effects After Anterior Cruciate Ligament Rupture. (August 2017) - Chang, Nai-Jen; Lee, Kuan-Wei; Chu, Chih-Jou; Shie, Ming-You; Chou, Pei-Hsi; Lin, Chih-Chan; Liang, Peir-In
Background: Anterior cruciate ligament (ACL) injury is a well-known risk factor for the development of posttraumatic osteoarthritis (PTOA). However, whether using continuous passive motion (CPM) with or without additional treadmill exercise (TRE) in early ACL injury might provide chondroprotective effects and further decrease the risk of PTOA has yet to be determined. Hypothesis: CPM may offer an enhanced chondroprotective effect, but TRE may attenuate that effect due to the mechanical stress on the joint and inflammatory cytokines in the joint. Study Design: Controlled laboratory study. Methods: Thirty adult New Zealand White male rabbits were randomly allocated to sedentary (SED), CPM, TRE, or CPM+TRE groups. Each rabbit underwent an ACL transection (ACLT) on the right knee, with the contralateral knee used as an internal control (sham). The 4 joint surfaces (ie, medial and lateral femoral condyles and tibial plateaus) were evaluated 4 weeks after surgery for gross appearance, histological characteristics, and quantitative osteoarthritis (OA) scores. Results: Overall, at the end of testing, the CPM group experienced the best protective therapeutic effects in all compartments. In gross appearance, CPM resulted in normal articular surfaces, while the TRE and SED groups exhibited surface abrasion. Histological analysis showed significant differences in articular cartilage status. The CPM group had significantly better histological OA scores ( P < .01), corresponding to the smoothest cartilage surface and sound chondrocyte and collagen arrangement. This group also showed abundant glycosaminoglycan (GAG) content and a sound growth microenvironment, with significantly lower expression levels of the inflammatory cytokine tumor necrosis factor α and the apoptotic marker caspase 3. In contrast, the TRE and SED groups showed several features of damage: distinct graded cartilage abrasion; damaged collagen fibers, corresponding to noticeable collagen type X (osteoarthritic cartilage); reduced cartilage thickness; fewer cartilaginous cells; and the appearance of chondrocyte clusters. These groups also showed loss of GAG, corresponding to higher levels of inflammatory cytokines and apoptosis of articular chondrocytes. Furthermore, the CPM+TRE group displayed visible pathological changes in the superficial cartilage, indicating that early loading exercise may contribute to osteoarthritis. The sham treatment showed no difference in the changes in all compartments between groups. Conclusion: Immediate CPM therapy produces a superior in situ microenvironment for reducing the occurrence of PTOA after ACL injury without reconstruction in rabbits. Clinical Relevance: These data suggest that immediate application of CPM therapy may be necessary to create a sound microenvironment in joints and possibly to decrease the risk of PTOA without or while awaiting ACL reconstruction. In contrast, both early active loading exercise and inactivity lead to the development of PTOA.